CRISPR/Cas9-Mediated Editing of a NODULATION SIGNALING PATHWAY 1 Homolog Alters the Production of Strigolactones in Sunflower Roots - Maria A. Lebedeva; Maria S. Gancheva; Maksim R. Losev; Sofia V. Sokornova; Oleg S. Yuzikhin; Anna A. Krutikova; Kirill V. Plemyashov; Lyudmila A. Lutova (Agronomy)
Sunflower (Helianthus annuus L.) is specifically infected by an obligatory root parasitic plant Orobanche cumana Wallr. (sunflower broomrape), which causes significant losses of sunflower yield. Breeding of sunflower varieties resistant to broomrape is an important challenge for agriculture. However, the selection of new resistant sunflower varieties was accompanied by the emergence of new virulent races of broomrape, which overcame the effect of resistance genes. Unraveling the molecular mechanisms underlying the resistance to broomrape in sunflowers should facilitate the development of new sunflower varieties with complex resistance to broomrape using genome editing technology. Here, we used CRISPR/Cas9-mediated genome editing in sunflower hairy roots for a specific knock-out of the gene encoding a GRAS transcription factor (HaNSP1a), acting as a possible regulator of strigolactone biosynthesis, a class of phytohormones known to induce the germination of broomrape seeds. According to HPLC-IT-TOF/MS analysis, the levels of orobanchol were decreased in the genetically modified roots with knock-out of the HaNSP1a gene, whereas, in contrast, 5-deoxystrigol levels were increased in the roots with HaNSP1a knock-out, suggesting the role of HaNSP1a in the regulation of the strigolactone biosynthetic pathway. The experimental approach described here could be used in further studies to test the effect of gene knock-out on the development of resistance to O. cumana in sunflowers.